2014
DOI: 10.3892/mco.2014.320
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel, cisplatin and 5-fluorouracil adjuvant chemotherapy following three-field lymph node dissection for stage II/III N1, 2 esophageal cancer

Abstract: To determine the efficacy of postoperative adjuvant chemotherapy with docetaxel + cisplatin + 5-fluorouracil (DCF) in lymph node metastasis-positive esophageal cancer, we retrospectively analyzed 139 patients with stage II/III (non-T4) esophageal cancer with lymph node metastasis (1-6 nodes), who did not receive preoperative treatment and underwent three-field lymph node dissection in the Juntendo University Hospital between December, 2004 and December, 2009. The tumors were histologically diagnossed as squamo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Positive lymph node metastasis is often a factor indicating a poor prognosis, 27 and many trials on POCT versus surgery alone were limited to patients with lymph node positivity. Hashiguchi et al conducted a retrospective study to explore the efficacy of DCF regimens in patients with ESCC with lymph node metastasis, and the results suggested that OS could be significantly improved 28 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Positive lymph node metastasis is often a factor indicating a poor prognosis, 27 and many trials on POCT versus surgery alone were limited to patients with lymph node positivity. Hashiguchi et al conducted a retrospective study to explore the efficacy of DCF regimens in patients with ESCC with lymph node metastasis, and the results suggested that OS could be significantly improved 28 29 .…”
Section: Discussionmentioning
confidence: 99%
“…The high pCR rate might be explained by the fact that the TP regime was adopted in this study, whereas in the past CF was mostly adopted. More and more studies have reported that paclitaxel cell toxicity is effective for treating squamous cell carcinoma (SCC) 20. Based on the retrospective data and clinical experience, weekly paclitaxel was tolerable, might have been related to the high pCR rate.…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, Hashiguchi et al . from Japan evaluated the efficacy of postoperative docetaxel, cisplatin, and 5‐Fu (DCF) chemotherapy for 139 stage II/III N1/N2 ESCC patients, and showed that patients with lymph node metastasis could possibly benefit from postoperative chemotherapy . In the same year, Lyu et al .…”
Section: Discussionmentioning
confidence: 99%